WHAT MOTHERS KNOW ABOUT NEONATAL TRIAGE - Ediálida Costa Santos; Maria Aparecida Munhoz Gaíva; Janaina Gomes dos Santos; Simone Mourão Abud (Universidade Federal do Paraná, 2011)
Neonatal triage, commonly known as the 'heel prick test', permits the tracing of individuals with probability of presenting certain determined pathologies, and the making of a diagnosis at an early stage and instituting specific treatments, in order to avoid serious consequences and increase the survival time of the ill. This was a descriptive study, with a quantitative approach, carried out with 55 new mothers with prior births, whose data were collected via semi-structured questionnaires and had as objective to analyse the mothers' knowledge in relation to neonatal triage. The results indicate that they have little knowledge in respect to neonatal triage, although the majority were familiar with the exam being carried out on their children; they did not know the ideal age for the triage to be made, and received information from the nurses about the test at the moment of discharge from hospital. This being so, it becomes necessary to include the subject in the pre-natal consultancies and to re-think the advisory methods used with the mothers.